Central America : Economic Progress and Reforms - Desruelle, Dominique (Departmental Papers; Departmental Paper, 2008)
Central America has made substantial progress in recent years in moving economic reforms forward and deepening regional and global integration. As result of these efforts, the region has experienced higher growth, increased capital inflows, and some reductions in poverty rates. But Central America remains vulnerable to adverse shocks and continues to face widespread poverty. While today Central America is in better condition to face such shocks, the current turmoil in global financial markets and U.S. growth slowdown could put at risk the hard-won gains of recent years. Faced with these challenges, the authorities are monitoring developments closely and are taking precautionary measures, but they also need to continue implementing productivity-enhancing reforms and measures aimed at reducing income inequality and poverty.